Conditional Knockout of Cav2.1 Disrupts the Accuracy of Spatial Recognition of CA1 Place Cells and Spatial/Contextual Recognition Behavior - Jung, Dahee; Hwang, Yu J.; Ryu, Hoon; Kano, Masanobu; Sakimura, Kenji; Cho, Jeiwon (Frontiers in Behavioral Neuroscience, 2016)
Hippocampal pyramidal neurons play an essential role in processing spatial information as implicated with its place-dependent firing. Although previous slice physiology studies have reported that voltage gated calcium channels (VGCCs) contribute to spike shapes and corresponding firing rate in the hippocampus, the roles of P/Q type calcium channels (Cav2.1) underlying neural activity in behaving mice have not been well investigated. To determine physiological and behavioral roles of Cav2.1, we conducted place cell recordings in CA1 and hippocampus dependent learning/memory tasks using mice lacking Cav2.1 in hippocampal pyramidal neurons under CamK2α-Cre recombinase expression. Results suggested that impairments shown in behavioral tasks requiring spatial and contextual information processing were statistically significant while general neurological behaviors did not differ between groups. In particular, deficits were more profound in recognition than in acquisition. Furthermore, place cell recordings also revealed that the ability to recollect spatial representation on re-visit in the conditional knockout was also altered in terms of the cue recognition while the capability of a place cell to encode a place was intact compared to the control group. Interestingly, CA1 pyramidal neurons of conditional knockout mice showed reduced burst frequency as well as abnormal temporal patterns of burst spiking. These results provide potential evidence that Cav2.1 in hippocampal pyramidal cells modulates temporal integration of bursts, which, in turn, might influence the recognition of place field and consequently disrupt spatial recognition ability.